Social Media Marketing, Fintech Knowledge, Perceived Risk on Intention to Use Islamic Fintech: The Moderating Role of Sharia Compliance Among Generation Z - Salsabilla Firzinia Aulia; Harun Alrasyid; Ratna Tri Hardaningtyas (EKONOMIKA SYARIAH : Journal of Economic Studies, 2026)
The rapid growth of Islamic financial technology (fintech) presents significant opportunities to enhance financial inclusion, particularly among Generation Z, who are highly exposed to digital platforms. However, the determinants of their intention to adopt sharia fintech remain insufficiently understood, especially when integrating social, cognitive, and risk-related factors. This study aims to examine the influence of social media marketing, fintech knowledge, and perceived risk on the intention to use Islamic fintech, with sharia compliance as a moderating variable. A quantitative approach was employed using survey data collected from 219 Generation Z respondents, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that social media marketing and fintech knowledge significantly influence intention, while perceived risk does not. Furthermore, sharia compliance does not moderate the effects of social media marketing and fintech knowledge but plays a significant buffering role in reducing the negative impact of perceived risk. These findings suggest that digital exposure and knowledge are key drivers of adoption, while religious compliance enhances trust by mitigating perceived risk.